World Economic Outlook, April 2013 : Hopes, Realities, Risks. (World Economic Outlook; World Economic Outlook ;, 2013)
Global economic prospects have improved again, but the bumpy recovery and skewed macroeconomic policy mix in advanced economies are complicating policymaking in emerging market economies. Chapter 3 examines the prospects for inflation, particularly because inflation was remarkably stable in the wake of the Great Recession and, in fact, has become less responsive to cyclical conditions. Chapter 4 examines whether today's fast-growing, dynamic low-income countries are likely to maintain their momentum and avoid the reversals that afflicted many such countries in the past.